Transformational Leadership Style, Transactional Leadership Style and Job Satisfaction - Karim, Latief (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
This study aimed to determine and analyze the effect of transformational and transactional leadership styles on job satisfaction at PT. Bank Rakyat Indonesia Regional Office Jayapura. The population in this study were employees of at PT. Bank Rakyat Indonesia Regional Office Jayapura, totaling 120 employees. The number of samples used was 55 people, determined based on the Slovin formula. The data source used is primary data, namely data collected directly by researchers from respondents using questionnaire instruments. The data analysis method that will be carried out consists of descriptive statistical analysis, validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, hypothesis testing through multiple linear regression analysis, partial test, simultaneous test, and determination coefficient test. The results of this study indicate that partially Transformational and Transactional Leadership Styles have a positive and significant effect on employee. Meanwhile, the Transactional Leadership Style has a dominant influence on the job satisfaction.